JOHN CALVIN DAN PERJAMUAN KUDUS: SEBUAH PROPOSAL BAGI PRAKTIK DI GEREJA BETHEL INDONESIA: Sebuah Proposal Bagi Praktik di Gereja Bethel Indonesia - Daniel Winardi (The Way: Jurnal Teologi dan Kependidikan, 2023)
This research intends to give a proposal concerning the practice of the holy communion in Gereja Bethel Indonesia (GBI) based on John Calvin’s theological thought. As one of the largest Pentecostal church in Indonesia and even further, as a Holy Spirit-centered church, GBI has not yet given a ‘room’ for Holy Spirit to unite the church with Christ through holy communion. In general, the holy communion practice is done as a memorial act upon His crucifixion that not only save the world, but also able to heal physical ailments. This study is using literature study to explore some material sources from GBI that contain the church’s doctrine, the primary source of John Calvin’s theological idea from his writings, and also secondary sources from theologians that has been exploring this issue. The researcher’s perspective and experience of being a member of GBI also cannot be dismissed to contribute in this study. I argue two things: 1) that Calvin’s theology on ‘spiritual presence’ about the union with Christ through the work of the Holy Spirit can be a beneficial contribution to the practice of the holy communion in GBI and it is not conflicting each other, considering the work of the Holy Spirit is a central doctrine in the life of Pentecostal congregation; 2) The act of faith in the GBI context might be a necessary role in believing the work of the Holy Spirit in holy communion. Researcher also give some potential challenges and solutions to consider in doing this proposal.